Association between heart rhythm and cortical sound processing - Marcomini, Renata S.; Frizzo, Ana Claúdia F; de Góes, Viviane B.; Regaçone, Simone F.; Garner, David M.; Raimundo, Rodrigo D.; Oliveira, Fernando R.; Valenti, Vitor E. (IMR Press, 2018)
Processing of sound signals is an important factor for conscious human communication and such sound signals may be assessed through cortical auditory evoked potentials. Heart rate variability provides information about heart rate autonomic regulation. The association between resting heart rate variability and cortical auditory evoked potentials was investigated. Resting heart rate variability in the time and frequency domain and the cortical auditory evoked potential components were investigated. Subjects remained at rest for 10 minutes for recording of heart rate variability. Cortical auditory evoked potential examinations were then undertaken through frequency and duration protocols in both ears. Linear regression indicated that the amplitude of the N2 wave of the cortical auditory evoked potentials in the left ear (not right ear) was significantly influenced by the standard deviation of normal-to-normal heart beats (17.7%) and percentage of adjacent heart beat intervals with a difference of duration greater than 50 milliseconds (25.3%) for the time domain heart rate variability indices in the frequency protocol. In the duration protocol and in the left ear the latency of the P2 wave was significantly influenced by low (20.8%) and high frequency bands in normalized units (21%) and low frequency/high frequency ratio (22.4%) indices of heart rate variability spectral analysis. The latency of the N2 wave was significantly influenced bylow frequency (25.8%), high frequency (25.9%) and low frequency/high frequency ratio (28.8%). In conclusion, it is proposed that resting heart rhythm is associated with thalamo-cortical, cortical-cortical and auditory cortex pathways involved with auditory processing in the right hemisphere.
Keywords: Autonomic nervous system; cardiovascular physiology; heart rate variability; neurophysiology; sound; speech